Synergy and Antagonism of Active Constituents of ADAPT-232 on Transcriptional Level of Metabolic Regulation of Isolated Neuroglial Cells - Panossian, Alexander G.; Hamm, Rebecca; Kadioglu, Onat; Wikman, Georg C.; Efferth, Thomas (Frontiers in Neuroscience, 2013)
Gene expression profiling was performed on the human neuroglial cell line T98G after treatment with adaptogen ADAPT-232 and its constituents – extracts of Eleutherococcus senticosus root, Schisandra chinensis berry, and Rhodiola rosea root as well as several constituents individually, namely, eleutheroside E, schizandrin B, salidroside, triandrin, and tyrosol. A common feature for all tested adaptogens was their effect on G-protein-coupled receptor (GPCR) signaling pathways, i.e. cAMP, phospholipase C and phosphatidylinositol signal transduction pathways. Adaptogens may reduce the cAMP level in brain cells by downregulation of adenylate cyclase gene ADC2Y and upregulation of phosphodiestherase gene PDE4D that is essential for energy homeostasis as well as for switching from catabolic to anabolic states and vice versa. All tested adaptogens up-regulated the PLCB1 gene, which encodes phosphoinositide-specific phospholipase C (PLC) and phosphatidylinositol 3-kinases (PI3Ks), key players for the regulation of NF-B-mediated defense responses. Other common targets of adaptogens included genes encoding ERα estrogen receptor(2.9-22.6 fold down-regulation), cholesterol ester transfer protein (5.1-10.6 fold down-regulation), heat shock protein Hsp70 (3.0-45.0 fold up-regulation), serpin peptidase inhibitor (neuroserpin), and 5-HT3 receptor of serotonin (2.2-6.6 fold down-regulation). These findings can be reconciled with the observed beneficial effects of adaptogens in behavioral, mental and aging-associated disorders. Combining two or more active substances in one mixture significantly changes deregulated genes profiles: synergetic interactions result in activation of genes that none of the individual substances affected, while antagonistic interactions result in suppression some genes activated by individual substances. Merging of deregulated genes array profiles and intracellular networks is specific to the new substance with unique pharmacological characteristics.